2007
DOI: 10.1902/jop.2007.060371
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review of Stress and Psychological Factors as Possible Risk Factors for Periodontal Disease

Abstract: Within the limitations of this systematic review, the majority of studies showed a positive relationship between stress/psychological factors and periodontal disease. However, in the future, well-designed and more representative studies should be considered to confirm these factors as a risk for periodontal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
215
0
19

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(240 citation statements)
references
References 44 publications
6
215
0
19
Order By: Relevance
“…The quality of the adjustment for confounding variables that could interfere with the course of the periodontal disease was evaluated by randomization, stratification, restriction, calibration and/or matching. These characteristics were classified as present or absent, which is in agreement with Peruzzo et al [9]. The specificity of the data indicating the randomization technique and the calibration value was required to be designated as present.…”
Section: Appraisal Of the Quality Of The Studiessupporting
confidence: 86%
See 3 more Smart Citations
“…The quality of the adjustment for confounding variables that could interfere with the course of the periodontal disease was evaluated by randomization, stratification, restriction, calibration and/or matching. These characteristics were classified as present or absent, which is in agreement with Peruzzo et al [9]. The specificity of the data indicating the randomization technique and the calibration value was required to be designated as present.…”
Section: Appraisal Of the Quality Of The Studiessupporting
confidence: 86%
“…Psychosocial stress is thought to play an important role in the etiology and progression of periodontal diseases, and the outcome of treatment [4,5]. The relationship between periodontitis and several dimensions of psychosocial distress such as stress, depression, anxiety, life events and poor coping reactions has attracted considerable attention from several groups of researchers during the last three decades [6][7][8][9]. A review showed a strong relationship between periodontal diseases and psychological factors such as stress, distress, anxiety, depression and loneliness [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…그 중 청소년의 구강건강과 건강행태의 위험요인의 하나 로 스트레스를 지목하였고 [9], 심리사회적요인 중 스트레 스가 치주질환의 잠재적 위험요인이라 보고한 바 있다 [10]. 국외의 연구에서는 Broadben [11] …”
Section: 서론unclassified